Three-dimensional structure of the rotavirus haemagglutinin VP4 by cryo-electron microscopy and difference map analysis. - Yeager, M (1994)
The three-dimensional structure of the rotavirus spike haemagglutinin viral protein 4 (VP4) has been determined to a resolution of 26 A by cryo-electron microscopy and difference analysis of intact virions and smooth (spikeless) particles. Native and spikeless virions were mixed prior to cryo-preservation so that both structures could be determined from the same micrograph, thereby minimizing systematic errors. This mixing strategy was crucial for difference map analysis since VP4 only accounts for approximately 1% of the virion mass. The VP4 spike is multi-domained and has a radial length of approximately 200 A with approximately 110 A projecting from the surface of the virus. Interactions between VP4 and cell surface receptors are facilitated by the bi-lobed head, which allows multi-site interactions, as well as the uniform distribution of the VP4 heads at maximum radius. The bi-lobed head is attached to a square-shaped body formed by two rods that have a slight left-handed helical twist. These rods merge with an angled, rod-like domain connected to a globular base approximately 85 A in diameter. The anchoring base displays pseudo 6-fold symmetry. This surprising finding may represent a novel folding motif in which a single polypeptide of VP4 contributes similar but non-equivalent domains to form the arms of the hexameric base. The VP4 spike penetrates the virion surface approximately 90 A and interacts with both outer (VP7) and inner (VP6) capsid proteins. The extensive VP4-VP7 and VP4-VP6 interactions imply a scaffolding function in which VP4 may participate in maintaining precise geometric register between the inner and outer capsids.(ABSTRACT TRUNCATED AT 250 WORDS)